2018
DOI: 10.1002/mbo3.529
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographical distribution of bacterial communities in Changbai Mountain, Northeast China

Abstract: The broad‐leaved and Korean pine mixed forest in Changbai Mountain, China is an important component of boreal forest; the area is sensitive to global climate change. To understand spatial distribution patterns of soil bacterial community along elevation, we analyzed the soil bacterial community diversity and composition along an elevational gradient of 699–1177 m in a primitive Korean pine forest in Changbai Mountain using the high‐throughput sequencing. In total, 149,519 optimized sequences were obtained. Bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 33 publications
(80 reference statements)
3
19
2
Order By: Relevance
“…Han et al [15] and Ping et al [3] concluded that bacterial and fungal communities showed a distance-decay relationship in Korean pine forest of Changbai Mountain. In fact, this conclusion did not quantify the relationship between community similarity and geographical distance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Han et al [15] and Ping et al [3] concluded that bacterial and fungal communities showed a distance-decay relationship in Korean pine forest of Changbai Mountain. In fact, this conclusion did not quantify the relationship between community similarity and geographical distance.…”
Section: Discussionmentioning
confidence: 99%
“…We sampled in September 2015. The method of sampling refers to Han et al [15]. All collected soil samples were sealed and refrigerated and then taken back to the laboratory.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed predominance of Basidiomycota and Ascomycota was not out of expectation due to the descriptions for these groups as general inhabitants for wetland and forest soils (Han et al., 2018; Sui, 2017). In addition, Ascomycota was more frequently identified in aquatic group than dryland group, while the Basidiomycota was more frequently identified in dryland group than aquatic group.…”
Section: Discussionmentioning
confidence: 85%
“…In this study, we provided a comprehensive characterization of fungal and bacterial communities along the crater margin of Tianchi Volcano, in Changbai Mountain Nature Reserve, by combing molecular and morphological analyses of culturable microbes, and metabarcoding analyses based on Illumina sequencing. A few previous studies have been conducted on microbial diversity in relatively lower altitudes of Changbai Mountain northern slope, mostly using high-throughput sequencing methods alone [ 14 , 33 , 55 ]. To the best of our knowledge, this study represents the first microbial community analysis in different sides of Tianchi Volcano crater margin, using integrated culture-dependent and metabarcoding approaches.…”
Section: Discussionmentioning
confidence: 99%